A method for determining the equivalent level L_eg - MAKAREWICZ, Rufin (Archives of Acoustics, 1977)
The constantly growing, traffic noise caused, among others, by the rapid development of motorization, is a considerable menace to the human environment. From the view point of acoustics the rating scale generally used to evaluate the environment is the equivalent level L_eq. In this paper the relationships between such parameters as the traffic flow, the speed and sound power of individual vehicles, and parameters describing the paths of the moving noise sources are derived.